Transfers, Social Safety Nets, and Economic Growth - Sala-i-Martin, Xavier (Washington, D.C. : International Monetary Fund, 1996)
This paper analyses the role of social safety nets in the form of redistributional transfers and wage subsidies. It is argued that public welfare programs can be viewed as a crime-preventing or disruption-preventing devices because they tend to increase the opportunity cost of engaging in crime or disruptive activities. It is shown that, in the presence of a leisure choice, wage subsidies may be better than pure transfers. Using a simple growth model, the optimal size of the public welfare program is found and it is argued that public welfare should be financed with income (not lump-sum) taxes, despite the fact that income taxes are distortionary. The intuition for this result is that income taxes act as a user fee on congested public goods and transfers can be thought of as productive public goods subject to congestion. Finally, using a cross-section of 75 countries, the partial correlation between transfers and growth is shown to be significantly positive.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet